An analytical study of (Smart Tennis Sensor) technical data and its relationship to the serving accuracy of wheelchair tennis players. - زينة عبد الكريم عباس; أ.د. فاطمة عبد مالح (الرياضة المعاصرة)
The study aimed to describe and analyze the technical data (Smart Tennis Sensor) for transmission accuracy in wheelchair tennis players and to identify the relationship between the technology data (Smart Tennis Sensor) and transmission accuracy in wheelchair tennis players. The researchers used the descriptive method of analysis and associative relationships . The research sample was selected from players with a local classification registered with the Wheelchair Tennis Association for the year (2020) in the intentional manner of (8 players) representing (25%) of the research community with a weight (63.8+1.26) kg, a height (171.2+1.09) meters, and an age (29.7+1.39) years. The researchers used the statistical bag (SPSS) to obtain the results of the research through: arithmetic mean, standard deviation, percentage law, torsion coefficient, and simple correlation coefficient. The results of the research showed a correlation between Smart Tennis Sensor data and transmission accuracy in wheelchair tennis players .The researchers recommended the adoption of this technique during training for wheelchair tennis players as this information gives instant feedback to the variables of each stroke and thus guide the player to the best performance